Fires at Neumark-Nord 2, Germany: An analysis of fire proxies from a Last Interglacial Middle Palaeolithic basin site. (2nd September 2016) - Pop, Eduard; Kuijper, Wim; van Hees, Erica; Smith, Geoff; García-Moreno, Alejandro; Kindler, Lutz; Gaudzinski-Windheuser, Sabine; Roebroeks, Wil
Abstract : Few sites with evidence for fire use are known from the Last Interglacial in Europe. Hearth features are rarely preserved, probably as a result of post-depositional processes. The small postglacial basins (<300 m in diameter) that dominate the sedimentary context of the Eemian record in Europe are high-resolution environmental archives often containing charcoal particles. This case study presents the macroscopic charcoal record of the Neumark-Nord 2 basin, Germany, and the correlation of this record with the distinct find levels of the basin margin that also contain thermally altered archaeological material. Increased charcoal quantities are shown to correspond to phases of hominin presence—a pattern that fits best with recurrent anthropogenic fires within the watershed. This research shows the potential of small basin localities in the reconstruction of local fire histories, where clear archaeological features like hearths are missing.